By Your Side - West, Kasie (New York, New York : HarperTeen, an imprint of HarperCollinsPublishers, 2017)
When Autumn finds herself locked in the library all weekend with Dax, a loner with a bad reputaton, shes surprised at the connection that develops between them.
660
Accelerated Reader
Keywords: Dating (Social customs); Juvenile fiction; Interpersonal relations in adolescence; Juvenile fiction; High schools; Juvenile fiction; Schools; Juvenile fiction; Dating (Social customs) -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction; Dating (Social customs) -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools; Fiction